What is the role of heat shock protein in abdominal organ transplantation? - Igor Lepski Calil; Francisco Tustumi; Jorge Henrique Bento de Sousa; Bruno Martins Tomazini; Ruy Jorge Cruz Jr; Gustavo Niankowski Saliba; Rafael Antonio Arruda Pécora; Luiz Augusto Carneiro D’Albuquerque (Einstein (São Paulo), 2022)
ABSTRACT Ischemia-reperfusion injury is a pathophysiological event occuring after abdominal organ transplantation, and has a significant influence on prognosis and survival of the graft. It is involved in delaying the primary function or non-functioning of the graft. The objective of this study was to provide information on heat shock protein mechanisms in ischemia-reperfusion injuries in abdominal organ transplantations, and to indicate the possible factors involved that may influence the graft outcome. Several classes of heat shock proteins are part of the ischemia and reperfusion process, both as inflammatory agonists and in protecting the process. Studies involving heat shock proteins enhance knowledge on ischemia-reperfusion injury mitigation processes and the mechanisms involved in the survival of abdominal grafts, and open space to support therapeutic future clinical studies, minimizing ischemia and reperfusion injuries in abdominal organ transplantations. Expression of heat shock proteins is associated with inflammatory manifestations and ischemia-reperfusion injuries in abdominal organ transplantations and may influence graft outcomes.